Lipopolysaccharide induced MAP kinase activation in RAW 264.7 cells attenuated by cerium oxide nanoparticles - Selvaraj, Vellaisamy (Data Brief, 2015)
High mortality rates are associated with the life threatening disease of sepsis. Improvements in septic patient survivability have failed to materialize with currently available treatments. This article represents data regarding a study published in biomaterials (Vellaisamy et al., Biomaterials, 2015, in press). with the purpose of evaluating whether severe sepsis mortality and associated hepatic dysfunction induced by lipopolysaccharide (LPS) can be prevented by cerium oxide nanoparticles (CeO2NPs) treatment in male Sprague Dawley rats. Here we provide the information about the method and processing of raw data related to our study publish in Biomaterials and Data in Brief (Vellaisamy et al., Biomaterials, 2015, in press; Vellaisamy et al., Data in Brief, 2015, in press.). The data contained in this article evaluates the contribution of MAPK signaling in LPS induced sepsis. Macrophage cells (RAW 264.7) were treated with a range of cerium oxide nanoparticle concentration in the presence and absence of LPS. Immunoblotting was performed on the cell lysates to evaluate the effect of cerium oxide nanoparticle treatment on LPS induced changes in Mitogen Activated Protein Kinases (MAPK) p-38, ERK 1/2, and SAPK/JNK phosphorylation.